Attitudes and knowledge of paediatric dentists' on digital radiography and cone beam computed tomography - (:unkn) unknown (PAKISTAN MEDICAL ASSOC, 2019)
Objective: To determine the frequency and reasons of digital radiography and cone-beam computed tomography usage among paediatric dental practitioners, and to assess their knowledge and need for specific education. Methods: The cross-sectional study was conducted from January to July 2017 and comprised paediatric dentists present at the European Academy of Paediatric Dentistry Interim Seminar in Turin, Italy, and members of the Turkish Society of Paediatric Dentistry who did not attend the event. Data about sociodemographics and their attitude towards, use of, and knowledge of digital radiography and cone beam computed tomography was collected by means of a 20-item questionnaire that was mailed to all the subjects. SPSS 22 was used to evaluate data. Results: Of the 435 questionnaires distributed, 245(56%) were returned, while 194 (45%) were deemed usable. The mean age of the responding paediatric dentists was 35.84 +/- 9.10 (range: 24-67 years) and 126(64.9%) were female. Users of digital radiography identified its advantages, such as lower radiation dose 166(85.7%), ease of image storage 150(77.3%), and the possibility to change image settings and to carry out measurements 106(54.5%). Overall, 70(36%) paediatric dentists had no knowledge of cone beam computed tomography. Dental trauma was cited as the reason for using cone beam computed tomography by 70(61.3%) subjects, dental development issues by 138(71%) and pathology in the jaws by 147(75.8%). Conclusion: Digital radiography and cone beam computed tomography users are increasing in the world.
Keywords: Paediatric dentistry; Digital radiography; Cone beam computed tomography; Use; Knowledge; DENTAL PRACTITIONERS